The Intrinsic rate of natural increase of Folsomia Candida (Willem), a parthenogenetic collembola = Laju pertambahan intrinsik populasi Folsomia candida (Willem), Collembola yang Partenogenetik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The intrinsic rate of natural increase for Folsomia Candida was calculated based on a cohort life table at 15.5Â°C. The value of r is .6085 per week. Compared to other species of Collemboia, the r value for F. Candida is exceptional/ high. This value will not be obtained from population in nature. Explanation could be found through their reactions to physical environment variation, food preference and predation.